Beyond the Pandemic: A Descriptive Analysis of Return Performance in Indonesia’s Healthcare Stocks - Nidrah Nidrah; Andi Nurfiana Haz; Fitriani Rahim (PT Maju Malaqbi Makkarana, 2026)
This study describes the return performance of selected healthcare stocks listed on the Indonesia Stock Exchange during the post-pandemic period. Using a quantitative descriptive design, monthly stock returns were calculated from closing prices for January 2021 to December 2025 and analyzed using mean, minimum, maximum, standard deviation, and cumulative return. The sample consists of eight healthcare-related firms representing pharmaceuticals, herbal and consumer health products, hospitals, and diagnostic services: KLBF, SIDO, TSPC, MIKA, HEAL, SILO, PRDA, and SAME. The results show heterogeneous return characteristics across firms. SILO records the highest mean monthly return at 3.00%, followed by SAME at 1.91%, HEAL at 1.56%, and TSPC at 1.34%. In contrast, SIDO and KLBF show negative average returns, while MIKA is nearly neutral. Risk dispersion is also evident: SAME, PRDA, and SILO exhibit the highest standard deviations, whereas TSPC records the lowest volatility. These findings indicate that healthcare stocks retain defensive relevance after the pandemic but are not homogeneous in risk-return behavior. The study provides an empirical descriptive profile for investors and academics without making causal claims.